Tinjauan Hukum Islam Tentang Kredit Pemilikan Rumah (Studi Kasus Di Perumahan Puncak Rabbany Mangkurakyat Kecamatan Cilawu Kabupaten Garut) - Wati, Ai; Patimah, Sipa Siti (STAI Al Musaddadiyah Garut, 2023)
With the existence of housing in the Garut area, people prefer to use the mortgage system or by way of credit, so far the provision of Home Ownership Loans is one of the activities of conventional banks that cannot be separated from interest. In the implementation of this mortgage, other units are involved, such as Limited Liability Companies (PT), which provide the location of land for house construction. This is stipulated in the mortgage such as selling prices, down payments, interest rates, monthly installments and other objects that must be paid by the debtor. The problem in this study is how the mechanism of Home Ownership Credit (KPR) in Puncak Rabbany Mangkurakyat Housing, Cilawu District, Garut Regency, and how the Islamic Law Review on KPR in Puncak Rabbany Mangkurakyat Housing, Cilawu District, Garut Regency. The purpose of this study was to learn more about the housing credit system in Puncak Rabbany Mangkurakyat housing in Kec. Cilawu Regency, Garut and analyze Islamic law on mortgages in Puncak Rabbany, Mangkurakyat, Cilawu District, Garut Regency. This research method is field research (filed Reseach) with a qualitative approach. The results showed that KPR was available at Puncak Rabbany Mangkurakyat Housing, Cilawu Regency District. Rabbany Peak Housing offers 2 contracts that consumers can choose from, including the Ijarah Mumtahia bit Tamlik (IMBT) and Al-Istishna' contracts, to the procedures for Rabbany Mangkurakyat Peak Housing, Cilawu Regency District are carried out on credit without any problematic contracts. In general, Sharia mortgages are applied in Garut in a way that is completely in accordance with the idea of mortgages in Islam, including explicit contracts, no interest or tadlis (fraud), no distribution delays, and no application of fines. Keywords: Islamic Law, KPR, IMBT & Al-Istishna